BENEFITS RESULTING FROM DEVELOPING LASTING RELATIONSHIPS WITH CUSTOMERS IN COMPANIES RENDERING SERVICES - Dorota Grego-Planer; Katarzyna Liczmańska; Joanna Petrykowska (Polityki Europejskie, Finanse i Marketing)
An increase in the importance of keeping customers and building their loyalty is conditioned by the changes dynamics that determines the occurrence of specific trends in the market environment of companies rendering services. The examples of such trends include intensification of competitiveness, market saturation, growing consumer demands, consumers’ increased access to modern technologies resulting in free use of information, which also means a possibility of comparing various market offers. As a consequence of the maintenance of the trends, companies rendering services are facing increasingly difficult problems related to finding new customers and they tend to use a maximum of the potential embedded in long-lasting relationships with customers. Lasting and close relationships with customers enable companies to gain numerous benefits primarily connected with improving communication, reducing costs, increasing turnover, and providing a better customer service. The objective of the present work is to present the results of the research conducted, among other things, on determining activities undertaken with a view to developing lasting relationships with customers in companies rendering services and functioning in Poland.